Strategi Manajemen Untuk Meningkatkan Daya Saing Lifestyle Café Ramah Lingkungan (Ecobrew Café) - Diyan Makom Al Akbar (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
Changes in urban consumption patterns, especially among millennials and Gen Z, show an increasingly strong tendency towards a sustainable lifestyle. A national survey shows that more than 78% of Indonesia's young generation has begun to adopt environmentally friendly practices, such as the use of reusable packaging and consumption of plant-based foods. Meanwhile, Indonesia still faces serious environmental challenges, with national waste generation reaching 72 million tons in 2023, of which around 40% is food and packaging waste (BPS, 2023). This context is an opportunity as well as a call for the F&B business sector, including cafés, to adopt sustainable practices. Through SWOT, PESTLE, STP, and 4P strategy analysis, it is known that Eco-Brew Café's strength lies in its sustainability values, community involvement, and strategic packaging that is adaptive to social trends and environmental regulations. However, challenges such as high operational costs and a limited market require appropriate mitigation strategies, including local collaboration, ongoing education, and inclusive product innovation for various consumer segments. Green marketing and storytelling strategies have also proven effective in building an image and increasing purchasing interest.